2003
DOI: 10.1177/15312445030414009
|View full text |Cite
|
Sign up to set email alerts
|

Pedophilia: Psychiatric Insights

Abstract: Sex offenses against children are considered the worst of cnrnes, even arnong cnminals thernselves. Attitudes have changed frorn blaming the victim to holding the perpetrator responsible for the actions. The prevalence of such offenses continues unabated despite the stigma for the offender and the irreparable trauma to the victim. Society and the medical and legal comrnunities have to present a more feasible definition ofthe problern, addressing specifically the acts that fdl under the term ofpedophilia. A pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 7 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…There could also be internal conflict as the guilt and shame they feel may make them want to talk, but if they talk they are less likely to be released. Sex offenders also find it difficult to be open and honest in an interview situation given the social condemnation and disgust often felt towards them (Bahroo, 2003;Gudjonsson, 2006). This could be due to uncertainty regarding the possible outcome of the interview, which may in turn cause the sex offender to be anxious.…”
Section: Use Of Empathymentioning
confidence: 99%
“…There could also be internal conflict as the guilt and shame they feel may make them want to talk, but if they talk they are less likely to be released. Sex offenders also find it difficult to be open and honest in an interview situation given the social condemnation and disgust often felt towards them (Bahroo, 2003;Gudjonsson, 2006). This could be due to uncertainty regarding the possible outcome of the interview, which may in turn cause the sex offender to be anxious.…”
Section: Use Of Empathymentioning
confidence: 99%
“…Moreover, the pedophilic action may be only watching a naked child (voyeuristic pedophile) or exposing oneself to the child (exhibitionist pedophile). Pedophilic action which involves touching may vary from only gentle touching of the child (frotteuristic pedophile) to penetration (Bahroo, 2005). Fagan et al (2002) also categorized their sexual actions regarding pedophiles' approach.…”
Section: Classificationmentioning
confidence: 99%
“…Studies also showed that around "25-40% of men attracted to children prefer boys" (Blanchard et al, 2000). While pedophilic individuals' primarily sexual interest is usually in boys who are older than 8 years old, child molesters are usually attracted to girls aged between 8 to 10-years-olds (Bahroo, 2005). Seto (2002) stated that pedophiles have multiple victims, low level of force or threat, and are unlikely to engage in nonsexual offenses.…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, numerous studies have demonstrated that a significant proportion of offenders are able to suppress penile responses (Howes, 1998;Kalmus & Beech, 2005;Marshall & Fernandez, 2000). Furthermore, the interpretation of arousal is difficult, as some offenders may not be aroused to a certain stimulus, while others may be aroused to deviant stimuli but are not known to be sexual offenders (Bahroo, 2003). Therefore, the problems with low responding (O'Donohue & Letourneau, 1992), along with the lack of reliability (Barbaree, Baxter, & Marshall, 1989) and validity (Hall, Proctor, & Nelson, 1988), have led some researchers to question the utility of this procedure with sexual offenders (Marshall & Fernandez, 2000).…”
Section: Introductionmentioning
confidence: 98%